Action research on the application of technology assisted urban gaming in language education in a Polish upper-secondary school. Issue 7 (3rd September 2018) - Pitura, Joanna; Terlecka-Pacut, Elżbieta
ABSTRACT: Being able to communicate in foreign languages, along with the remaining key competences for lifelong learning, are of special significance for upper-secondary school students – soon-to-be tertiary education students and employees. Although Polish educational authorities have made efforts to account for this need in the Core Curriculum for Modern Languages, the provisions are pursued with difficulty in school practice. The aim of this paper is to address this challenge by exploring and evaluating the feasibility and student-participant perceptions of urban gaming in school settings as a didactic tool that facilitates language education, as well as digital, social, and learning to learn skills development in an upper-secondary school. Accordingly, the paper presents the design, implementation and evaluation of a technology assisted urban game named 'As it once was in Cracow—discovering the history of the city', developed for a group of Polish upper-secondary school students ( N = 25) from Warsaw. The results provide evidence for student-perceived educational gains with regard to the development of skills such as teamwork, digital literacy, the English language, and content (history) knowledge.